Dynamic Variation Characteristics and Influential Factors of PM2.5 in Subway Platforms Under Air-conditioning Condition - Wang Lihui; Hu Tianwei; Zhang Jihua; Liu Jun; Zheng Yi; Song Jie; Pan Jun; Yang Jun; Fan Zier (Zhileng xuebao)
This study investigated some of the major factors influencing subway PM pollutants under air-conditioning conditions through field measurements and CFD simulations on a Shanghai subway station. Based on the principle of the air-conditioning system, the particle concentrations at the air supply outlet, return air outlet and the screen door creates a direct impact on particle concentration of the platform. Dust accumulation at the fresh air shaft is found to be a secondary dusting action when the fresh air is supplied, which leads to ahigher particle concentration in the subway station than that in outdoor air. Each factor’s influence on the platform particle concentration was analyzed through the orthogonal test. Results confirmed that the particle concentrations at air outlet and platform screen door, along with the supply air and return air velocity, significantly influenced theparticle concentration at platform; while the temperature ofsupplyair , platform screen door and the platform has little impacts on the particle concentration at platform.